Responsabilidade fiscal e desenvolvimento municipal: estudo com dados em painel dos municípios brasileiros de 2006 a 2013 - Menezes, Itamar Pordeus Fernandes de (2017)
This paper proposes a discussion about the relationship between public spending and economic development in Brazilian municipalities from 2006 to 2013. In the Brazilian context, the role of municipalities in promoting development grew exponentially with the decentralization implemented through the Federal Constitution of 1988, both directly and indirectly with projects and programs in partnership with other federative entities or with other institutions, presenting an increasing importance in the national scenario. The relevance of this study lies in the discussion of the balance of the municipal public accounts through three pillars fundamental to any public manager of any level of power, such as: fiscal responsibility, accountability practices and transparency in the application of public resources. These pillars are based on the Law of Fiscal Responsibility - LRF, a kind of code of conduct for public managers, in which discipline and limits their performance in the treatment of public expenditures. In addition, it is important to analyze the correlation of indicators that measure the quality of fiscal management and municipal development to see if the assertion that the quality of fiscal management is directly related to municipal development presents coherence and causality. The main objective of this master thesis is to evaluate the correlation between municipal public fiscal management indicators and development indicators of Brazilian municipalities. The research is characterized as descriptive and explanatory regarding the objectives, bibliographical and documentary regarding the procedures and quantitative regarding the approach of the problem. Estimates were made to verify how fiscal variables influence economic development variables, considering the pattern of municipal public spending and which there are many poorly developed municipalities in Brazil. The data, of annual measurement, were obtained from the Federation of Industries of the State of Rio de Janeiro FIRJAN website, which was based on official information. The analysis of the data pointed to a low but regular development, over time, with the growth in education and health indicators and the decrease in employment and income generation in the municipalities. The classification of fiscal management was classified as regular, with a moderate increase in personnel expenses and a reduced capacity to generate own revenues. The results obtained by regressions with panel data are considered coherent with the theory, leading to the understanding that municipal public fiscal management has an influence on municipal development indicators.